The Elderly Poor in Rural Ontario: Inmates of the Wellington County House of Industry, 1877-1907 - Stewart, Stormie (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1992)
AbstractLate in the nineteenth century, a number of Ontario county governments financed and built social welfare institutions. Essentially modelled after English and American work-houses, these institutions were intended to provide indoor relief to all indigent members of the community. By the turn of the century, however, the inmate population was almost uniformly elderly. This paper traces the demographic evolution of one such institution, the Wellington County House of Industry, and examines the circumstances and problems, frequently gender-specific, which compelled aged men and women to enter.